Pre-Clinical Proof of Concept: Intra-Carotid Injection of Autologous CD34-Positive Cells for Chronic Ischemic Stroke - Ogawa, Yuko; Okinaka, Yuka; Kikuchi-Taura, Akie; Saino, Orie; Tani-Yokoyama, Ayumi; Masuda, Satoru; Komatsu-Horii, Miki; Ikemoto, Yoshihiko; Kawamoto, Atsuhiko; Fukushima, Masanori; Taguchi, Akihiko (Frontiers in Medicine, 2022)
This study was conducted to evaluate the safety and efficacy of human peripheral blood CD34 positive (CD34+) cells transplanted into a murine chronic stroke model to obtain pre-clinical proof of concept, prior to clinical testing. Granulocyte Colony Stimulating Factor (G-CSF) mobilized human CD34+ cells [1×104 cells in 50 µL phosphate-buffered saline (PBS)] were intravenously (iv) or intra-carotid arterially (ia) transplanted four weeks after the induction of stroke (chronic stage) and neurological function was evaluated. In this study, severe combined immune deficiency (SCID) mice were used to prevent excessive immune response after cell therapy. Two weeks post cell therapy, the ia CD34+ cells group demonstrated a significant improvement in neurological functions compared to the PBS control. The therapeutic effect was maintained eight weeks after the treatment. Even after a single administration, ia transplantation of CD34+ cells had a significant therapeutic effect on chronic stroke. Based on the result of this pre-clinical proof of concept study, a future clinical trial of intra carotid artery autologous peripheral blood CD34+ cells administration in the intra-carotid artery for chronic stroke patients is planned.